PENERAPAN STANDAR OPERASIONAL PROSEDUR PEMBERSIHAN KAMAR DI SARI ATER HOTEL AND RESORTS: - Heri Sutardi; Albarr Danendra (Akademi Pariwisata NHI Bandung, 2025)
In this study, the focus is on the Implementation of Standard Operating Procedures for Room Cleaning at Sari Ater Hotel and Resorts. Where the Implementation of good Standard Operating Procedures is very important to increase guest satisfaction and produce employee performance and create a good hotel image. The collection method used is a quantitative method. The data collection technique used is by distributing questionnaires, observation. While the data analysis technique uses a Likert scale. Problems in the study: 1. How is the implementation of the preparation of Standard Operating Procedures for room cleaning at Sari Ater Hotel and Resort? 2. How is the implementation of the Standard Operating Procedure process for room cleaning at Sari Ater Hotel and Resort? 3. How is the implementation of the finishing of Standard Operating Procedures for room cleaning at Sari Ater Hotel and Resort? The suggestions given for solving the problem are: Based on the conclusions above, it can be seen that there are still several problems concerning the implementation of Standard Operating Procedures by room attendants at Sari Ater Hotel and Resorts, therefore the author provides several suggestions so that they can be considered to improve and overcome obstacles that occur during the process of implementing Standard Operating Procedures in order to increase guest satisfaction during their stay Keywords: implementation, SOP